Microbiological and physicochemical stability of raw, pasteurised or pulsed electric field-treated milk. (December 2016) - McAuley, Catherine M.; Singh, Tanoj K.; Haro-Maza, José Fernando; Williams, Roderick; Buckow, Roman
Abstract: Pulsed electric field (PEF) processing was investigated as an alternative dairy preservation technology that would not compromise quality yet maintain safety. PEF processing of raw whole milk (4% fat) was conducted at two processing conditions (30 kV/cm, 22 μs, at either 53 or 63 °C outlet temperature) and compared with two thermal treatments (15 s, at either 63 or 72 °C) and a raw milk control and replicated twice. Milk bottles (2 L) from each treatment were incubated for two weeks, at 4 and 8 °C, and assessed for total plate count, pH, colour, rennetability, plasmin activity and lipid oxidation. The microbial quality of the thermal (72 °C/15 s) and PEF (63 °C) were similar. A drop in pH occurred after a change in counts was observed. Rennetability was not different between the treatments. Short chain acids dominated the volatile profile of the milk samples. Concentration of volatiles derived from microbial activity, namely 2, 3-butanedione, acetic acid and other milk lipid derived short chain free fatty acids (e.g. butanoic and hexanoic acids), followed the trend of microbial activity in milk samples. Industrial relevance: Research on the application of PEF to control spoilage and pathogenic microorganisms and enzyme systems in milk spans a wide array of processing equipment and reaction conditions. While industrial scale PEF processing of liquid milk for preservation and improved quality seems generally possible, substantiation of lower thermal damage under safe and scalable PEF conditions is required to enable economic feasibility. Highlights: PEF treatment of whole milk at 30 kV/cm for 22 s and 53–63 °C Tmax was investigated. Shelf life of PEF treatment milk at 63 °C was similar to thermal pasteurisation. Physicochemical properties of milk were not affected by PEF treatment. Increase of short chain free fatty acids was related to microbial growth.